Patterns of innervation of the lacrimal gland with clinical application. Issue 8 (4th August 2014) - Scott, Gabriel; Balsiger, Heather; Kluckman, Matthew; Fan, Jerry; Gest, Thomas
<x xml:space="preserve">Abstract</x> Parasympathetic stimulation of the lacrimal gland is responsible for tear production, and this innervation originates from fibers conveyed in the facial nerve. After synapse in the pterygopalatine ganglion, postsynaptic parasympathetic fibers travel within the zygomatic and zygomaticotemporal nerves (ZTN) into the orbit. As described in most anatomy texts, ZTN communicates with the lacrimal nerve (LN) posterior to the gland and then secretomotor fibers enter the gland. This study was performed to gain a better understanding of the innervation of the lacrimal gland. Seventeen cadaver heads were bisected for a total of 34 sides, which then underwent dissection of the superolateral orbital region to observe the course for the LN and ZTN. Three variations of the course of the LN and ZTN were found. In 20 (60.6%) dissections it was documented that the ZTN entered directly into the lacrimal gland with no communication with the LN. In 12 (36.4%) of the bisected heads, ZTN had both a direct connection into the gland and a communicating branch with the LN. In only one (3.0%) bisected head, ZTN communicated with the LN before entering the gland as it is commonly described in anatomy texts. Our study reveals that the ZTN usually takes a different course than is classically described in most anatomy textbooks. A greater understanding of the typical course these nerves take may help surgeons identify them more easily and avoid damaging them. Clin. Anat. 27:1174–1177, 2014. © 2014 Wiley Periodicals, Inc.